Criteria to Characterize Polypoid Nodule Scar after Gastric Endoscopic Submucosal Dissection in Order to Differentiate It from Tumor Recurrence - Vitor Arantes; Noriya Uedo (Turkish Journal of Gastroenterology, 2021)
Cite this article as: Arantes V, Uedo N. Criteria to characterize polypoid nodule scar after gastric endoscopic submucosal dissection in order to differentiate it from tumor recurrence. Turk J Gastroenterol. 2021; 32(1): 106-107.